Expression of regulatory receptors on gamma delta T Cells and their cytokine production in Behcet's disease - DİRESKENELİ, RAFİ HANER (BIOMED CENTRAL LTD, 2013)
Introduction: Behcet's disease (BD) is a multi-systemic disorder with muco-cutaneous, ocular, arthritic, vascular or central nervous system involvement. The role of gamma delta T cells is implicated in BD. The activation status of gamma delta T cells and their cytokine secretion against phosphoantigens are evaluated in BD. Methods: NKG2A, NKG2C, NKG2D, CD16 and CCR7 molecules on gamma delta T cells were analyzed in 70 BD, 27 tuberculosis (TB) patients and 26 healthy controls (HC). Peripheral gamma delta T cells were expanded with a phosphoantigen (BrHPP) and IL-2, restimulated with BrHPP and a TLR3 ligand, and cytokine production was measured. Results: gamma delta T cells were not increased in both BD and TB patients, but the proportions of TCRV delta 2(+) T cells were lower (58.9 and 50.7 vs. 71.7%, P = 0.04 and P = 0.005) compared to HC. Higher proportion of TCRV delta 2(+) T cells were CD16(+) (26.2 and 33.9 vs. 16.6%, P = 0.02 and P = 0.001) and CCR7(-) (32.2 and 27.9 vs. 17.7%, P < 0.0001 and P = 0.014) in BD and TB patients compared to HC. NKG2C(+) gamma delta(+) T cells were relatively increased (0.5 and 0.6 vs. 0.3%, P = 0.008 and 0.018), whereas NKG2D positivity was decreased in patients with BD and TB (77.7 and 75.8 vs. 87.5%, P = 0.001 and 0.004). Expansion capacity of gamma delta T cells in BD and TB as well as production of IL-13, IFN-gamma, granulocyte monocyte colony stimulating factor (GM-CSF), TNF-alpha, CCL4 and CCL5 in BD was lower compared to HC, when restimulated by TLR3 ligand and BrHPP. Conclusion: The changes on gamma delta T cells of BD as well as TB patients implicate that gamma delta T cells have already been exposed to regulatory effects, which changed their activity. Lower cytokine response of gamma delta T cells implicates down modulation of these cells in BD.
Keywords: MHC CLASS-I; PERIPHERAL-BLOOD; MYCOBACTERIUM-TUBERCULOSIS; ISOPENTENYL PYROPHOSPHATE; IMMUNE-RESPONSE; LYMPHOCYTES; ACTIVATION; EFFECTOR; ANTIGENS; CHEMOKINES